Providing feedback in simulated investigative interviews with adult witness avatars increases the use of free recall and open questions - Tohvelmann, Mari-Liis (International journal of police science & management, 2025)
Previous research has indicated that investigative interviews with adult victims and witnesses are often of low quality. Earlier findings also indicate that interviewing skills exhibit improvement when the interviewers are given feedback on their performance. Technological innovations make it possible to implement such an approach in a scalable manner. Simulated interviews with child avatars have shown that repeated feedback improves the proportion of recommended questions in those interviews. We created adult witness avatars (AWA) to simulate investigative interviews with adult victims and witnesses. We examined whether avatar interviews coupled with feedback (vs no feedback) would result in improvements in interview quality. Of the 60 participants, half received process feedback after each of four simulated interviews. The avatars revealed predefined memories and made errors as a function of algorithms formulated based on previous empirical research on the response behavior of adult witnesses in experimental studies. Results showed that receiving feedback after the simulated interviews increased the proportion of recommended questions (free recall and open questions) in avatar interviews compared with not receiving feedback (90.3% vs 72.6%, respectively). There was also a significant correlation between the question types and accuracy of details, even when analyzed separately for feedback and control groups. We demonstrated that with feedback after each AWA interview, the proportion of recommended questions was significantly higher in the AWA group than in the control group. The implications for practice are discussed.